Manifestações clínicas, bioquímicas, ultrassonográficas e metabólicas da síndrome dos ovários policísticos em adolescentes - Rehme, Marta Francis Benevides [UNESP]; Pontes, Anaglória [UNESP]; Goldberg, Tamara Beres Lederer [UNESP]; Corrente, José Eduardo [UNESP]; Pontes, Anaglória [UNESP] (FapUNIFESP (SciELO), 2013)
PURPOSE: To evaluate the clinical, ultrasonographic, biochemical and metabolic alterations of adolescents with polycystic ovary syndrome (PCOS). METHODS: Retrospective observational study conducted on 44 adolescents aged 12 to 19 years, diagnosed with PCOS according to the Rotterdam Consensus. Metabolic changes were assessed according to the recommendations of the International Diabetes Federation, considering: waist circumference (WC) ≥90th percentile (10-15 years of age) or >80 cm (age >16 years), fasting glucose >100 mg/dL, triglycerides >150 mg/dL, HDL <40 mg/dL, and blood pressure ≥Hg 130/85 mm. RESULTS: Mean age was 16.7±2.2 years and age at menarche was 11.8±1.4 years. The menstrual irregularity most frequently observed was amenorrhea (72.7%) followed by oligomenorrhea (27.3%); hirsutism was observed in 86.4% and acne in 56.8%. Polycystic ovaries were observed by ultrasound only in 27.3%. Mean BMI was 30.3±6.6 kg/m2. According to BMI, 52.3% of adolescents were obese, 13.6% were overweight and 6.8% had a healthy weight. Increased waist circumference (63.6%, 28/44) and the reduction of HDL-C (34.1%, 15/44) were the metabolic changes most frequently observed. Increased triglycerides were observed in 27.3% (12/44) and increased blood pressure and impaired fasting glucose were found in 9.1% (4/44) and 4.5% (2/44) of cases, respectively. Acanthosis nigricans was observed in 52.3% and insulin resistance in 62.8% of the adolescents with PCOS. Metabolic syndrome was identified in six children (13.6%), all of them obese or overweight. CONCLUSION: In the adolescents with PCOS studied here, menstrual irregularity and hirsutism were the most common clinical manifestations, while the sonographic findings consistent with polycystic ovaries were less prevalent. Obesity associated with insulin resistance predisposes these adolescents to a higher frequency of metabolic disorders.
Clinical manifestations, biochemical, ultrasonographic and metabolic of polycystic ovary syndrome in adolescents
Keywords: Adolescent; Hyperandrogenism; Insulin resistance; Metabolic syndrome X; Polycistic ovary syndrome